Phosphoinositide 3-kinases and the regulation of platelet function. (1st April 2004) - Jackson, S.P.; Yap, C.L.; Anderson, K.E.
Abstract : A clear understanding of the role of PI (phosphoinositide) 3-kinases in supporting the haemostatic function of platelets has been slow to evolve. In fact, insight into the roles of individual PI 3-kinase isoforms in platelet function remains rudimentary. However, based on in vitro studies using wortmannin and LY294002, there is evidence for an important role for PI 3-kinases in regulating a broad range of functional platelet responses, including primary platelet adhesion, cytoskeletal remodelling and platelet aggregation. One of the critical platelet responses involves affinity regulation of the major platelet integrin αIIbβ3, the primary receptor mediating platelet aggregation and thrombus growth. The input signals regulating integrin αIIbβ3 can be divided into three main groups: (1) Gq -coupled receptors linked to the activation of PLCβ (phospholipase Cβ); (2) Gi -coupled receptors linked to the regulation of adenylate cyclase and Rap1b; and (3) adhesion receptor signalling involving Src kinase-dependent activation of PLCγ isoforms. PI 3-kinases have not been demonstrated to play a critical role in Gq -dependent platelet activation; however, one or more PI 3-kinase isoforms appears to be important for Gi -dependent activation of Rap1b and adhesion receptor activation of PLCγ isoforms. Thus distinct co-operative PI 3-kinase signalling mechanisms appear to play an important role in regulating the adhesive function of integrin αIIbβ3.